2022
DOI: 10.3389/fmicb.2022.893071
|View full text |Cite
|
Sign up to set email alerts
|

The International Space Station Environment Triggers Molecular Responses in Aspergillus niger

Abstract: Due to immense phenotypic plasticity and adaptability, Aspergillus niger is a cosmopolitan fungus that thrives in versatile environments, including the International Space Station (ISS). This is the first report of genomic, proteomic, and metabolomic alterations observed in A. niger strain JSC-093350089 grown in a controlled experiment aboard the ISS. Whole-genome sequencing (WGS) revealed that ISS conditions, including microgravity and enhanced irradiation, triggered non-synonymous point mutations in specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 78 publications
(96 reference statements)
2
3
0
Order By: Relevance
“…Clusters associated with small molecule and peptide biosynthesis in fungi were found in abundance, reaffirming earlier studies into molecular responses to microgravity [11]. The pool of novel genes unique to the ISS species (Supplementary Table S12)…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Clusters associated with small molecule and peptide biosynthesis in fungi were found in abundance, reaffirming earlier studies into molecular responses to microgravity [11]. The pool of novel genes unique to the ISS species (Supplementary Table S12)…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, genes related to beta-mannosidase and mannose activities were up-regulated in high salinity media in the brine shrimp Artemia salina [33], suggesting that mannose and its derivatives may be accumulated as organic osmolytes. Clusters associated with small molecule and peptide biosynthesis in fungi were found in abundance, reaffirming earlier studies into molecular responses to microgravity [11]. The pool of novel genes unique to the ISS species (Supplementary Table S12) showed an abundance of genes related to peptide and small molecule synthesis, transmembrane secretion/transport, and mechanosensitive ion channels.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…84 Across animal, plant, and fungi kingdoms, SNPs associated with spaceflight have been reported. [84][85][86] In humans particularly, space radiation left SNPs that were known to be risk alleles for neuro-ocular issues, suggesting a potential functional consequence of these SNPs. 84 In bacteria, SNPs have been associated with the development of antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
“… 154 , 161 Subsequent experiments comparing the same A. niger exposed to the ISS conditions against a ground control revealed that ISS conditions permanently altered the strains metabolic functions with a significant enhancement in production of the pyranonigrin A. 162 A summary of fungal pathogens with medical astro-microbiology association can be seen in Table 3 .…”
Section: Spaceflightmentioning
confidence: 99%